Ethyl 1-tert-butyl-2-(4-methoxyphenyl)-1H-benzimidazole-5-carboxylate - Arumugam, Natarajan; Abd Hamid, Shafida; Abdul Rahim, Aisyah Saad; Hemamalini, Madhukar; Fun, Hoong-Kun (International Union of Crystallography, 2010)
In the title molecule, C21H24N2O3, the imidazole ring is essentially planar, with a maxium deviation of 0.015 (1) A ° . The dihedral angle between the benzene and imidazole rings is 65.47 (6). The crystal packing is stabilized by weak intermolecular C—H O and C—H N hydrogen bonds, forming zigzag chains along the c axis. The crystal structure is further stabilized by C—H interactions.